2004
DOI: 10.1111/j.1365-4632.2004.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of eosinophilic pustular folliculitis with topical tacrolimus

Abstract: We present two cases of Eosinophilic pustular folliclulitis (EPF) who were successfully treated with topical tacrolimus. Indomethacin is the most frequently used agent for the treatment of EPF, however, tacrolimus ointment may become the treatment of choice for patients with EPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Topical tacrolimus ointment 0·03% proved to be highly effective in both cases, providing rapid improvement in the eruption and the pruritus. Previous reports have demonstrated the usefulness and rapid onset of action of topical tacrolimus 0·1% in the treatment of adult EPF 7 but to our knowledge this treatment has not previously been described in the infantile form.…”
mentioning
confidence: 77%
“…Topical tacrolimus ointment 0·03% proved to be highly effective in both cases, providing rapid improvement in the eruption and the pruritus. Previous reports have demonstrated the usefulness and rapid onset of action of topical tacrolimus 0·1% in the treatment of adult EPF 7 but to our knowledge this treatment has not previously been described in the infantile form.…”
mentioning
confidence: 77%
“…It has been suggested that indomethacin, an inhibitor of cyclooxygenase activity, reduces the synthesis of an eosinophil chemotactic factor, which was isolated from skin in EPF 10 . Nowadays, topical tacrolimus ointment has been reported in the treatment of EPF 24–26 . However, no treatment modality has been reported to be consistently effective in this disease 10 …”
Section: Discussionmentioning
confidence: 99%
“…On one side, red hair melanin is characterized by high ratio of pheomelanin to eumelanin, 4 and it is well known that pheomelanin is a risk factor for skin cancer. On one side, red hair melanin is characterized by high ratio of pheomelanin to eumelanin, 4 and it is well known that pheomelanin is a risk factor for skin cancer.…”
Section: Red Hairs Number Of Nevi and Risk Of Cutaneous Malignant Mmentioning
confidence: 99%